Outcomes from a randomized controlled trial of a group intervention for HIV positive men and women coping with AIDS-related loss and bereavement. - Sikkema, Kathleen J; Hansen, Nathan B; Kochman, Arlene; Tate, David C; Difranceisco, Wayne (Death studies, 2004)
The purpose of this study was to examine the impact of a group coping intervention for HIV-positive men and women who have lost a loved one(s) to AIDS in the past 2 years. Two hundred thirty-five participants, diverse with respect to race/ethnicity and sexual orientation, were randomly assigned to a 12-week cognitive-behavioral group intervention or to an individual therapy on request comparison condition. Measures assessing grief and psychiatric distress were administered at baseline and 2 weeks post-intervention period. Although a strong gender effect was observed in outcome, both men and women participating in the group intervention demonstrated significantly more reduction in psychiatric distress than controls. Further, women in the group intervention demonstrated significant reductions in grief and depressive symptoms over men in both conditions and women in the comparison condition. Brief cognitive-behavioral group interventions for coping with grief have a positive impact on the psychiatric functioning of HIV-positive participants. This appears to be especially true for HIV-positive women; a group not previously focused on in clinical research related to AIDS bereavement.
Keywords: Adaptation, Psychological; Bereavement; Female; HIV Infections; Humans; Male; Psychotherapy, Group; Sex Factors; Stress, Psychological; Treatment Outcome; United States